(untitled) (Gestión y Gerencia, 2023)
Within the current context of progressive recovery of business activities, after the sanitary emergency due to coronavirus Covid-19, small and medium-sized companies face a more complex, dynamic, transformed and uncertain environment, which is why this essay is intended, analyze the emerging approaches that they can take advantage of, to strengthen their management system and help them achieve their objectives. In this essay an analysis of documentary research is made, on the main organizational aspects that concern this type of organizations. Among the findings obtained, it is worth highlighting the importance for small and medium-sized companies of having knowledge about strategic management, preventive management and systemic vision, to respond adequately to changes in the environment. In addition, information and communication technologies are essential means in these times of the 21st century, for interaction with customers and participation in a digital market that is developed largely through social networks. Additionally, it was found that having a management system adapted to the needs of the company contributes to its development, and participation in business cooperative activities allows them to form alliances, as well as reach other clients. Finally, a plan called SANAR is proposed, which includes five strategies, for the reactivation of small and medium-sized companies, in post-pandemic times by Covid-19.